2015
DOI: 10.1080/02626667.2015.1032293
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impact on agricultural production: the case of Comoe River basin in Ivory Coast

Abstract: The objective of this study is to assess the impact of climate change on the evolution of the hydrological balance of the Comoe basin, an area of rainfed agriculture. Starting from a frequency analysis of cropping season with an appraisement of cumulative water deficit through a daily water balance simulation, the study explores the impact of climate conditions evolution over the cropping season periods from 1950 to 2000. The agroclimatic performance indicators thus defined, particularly the satisfaction index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Savanna vegetation is responsive to both short-term fluctuations in rainfall and long-term climatic patterns (Goward & Prince, 1995;Scanlon et al, 2002). However, rainfall generally decreased in the region over the past 50 years (Noufé et al, 2015;Sagna et al, 2021), and we did not detect any significant trend in rainfall in the study area between 1981 and 2021 (see time series analysis of monthly precipitation in Supplementary Information). Vegetation shifts driven by increased rainfall are therefore unlikely.…”
Section: Was Defaunation Responsible For Vegetation Changes In Comoémentioning
confidence: 58%
“…Savanna vegetation is responsive to both short-term fluctuations in rainfall and long-term climatic patterns (Goward & Prince, 1995;Scanlon et al, 2002). However, rainfall generally decreased in the region over the past 50 years (Noufé et al, 2015;Sagna et al, 2021), and we did not detect any significant trend in rainfall in the study area between 1981 and 2021 (see time series analysis of monthly precipitation in Supplementary Information). Vegetation shifts driven by increased rainfall are therefore unlikely.…”
Section: Was Defaunation Responsible For Vegetation Changes In Comoémentioning
confidence: 58%
“…Several pieces of literature describe the ways farmers perceive climate change, including those of Amjath-Babu et al (2017) in South Asia and South America, [20] in Benin [21] in Central Rift Valley of Ethiopia, Nwaobiala & Nottidge [22] in the Abia State of Nigeria, Mngumi [23]in Mwanga district in northern Tanzania, Toukal Assoumana et al (2016) [24] in Niger, Asayehegn et al [25]. In Kenya, Atube et al, (2021) [26] in Uganda, and Noufé et al [27] in Comoe River basin in Ivory Coast. These studies collectively indicate that farmers have observed notable shifts and alterations in climate and weather patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Le climat constitue un facteur qui régit la production agricole et sa variabilité interannuelle conditionne les systèmes socioéconomiques et environnementaux liés à la disponibilité des ressources en eau (Djamanb et al, 2016 ;Faye, 2017). Ces irrégularités pluviométriques ont pour corollaire la variabilité des dates de démarrage, de fin et de durée des saisons pluvieuses, associées à une plus grande occurrence des déficits hydriques (Noufé et al, 2015). Les pluies représentent l'élément climatique fondamental qui conditionne les différentes activités agricoles, car les fluctuations climatiques entraînent une modification des systèmes culturaux, engendrent un déficit de la balance commerciale, ébranlent le système économique et tout le tissu social (Djohy et al, 2015).…”
Section: Introductionunclassified